PENGARUH INDIKATOR MAKRO EKONOMI DAN FAKTOR GLOBAL TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) - Moh Maulidi Syarif; Nadia Asandimitra (Kompetensi (Competence : Journal of Management Studies), 2015)
The purpose of this study was to analyze the effect of macroeconomic indicators and global factors to IHSG period 2005-2014. Macroeconomic indicators used in this study are inflation rate, SBI rate and Exchange rate of rupiah to dollar. The global factors used include world oil price, world gold price and The Fed rate. The analytical method used in this study is multiple regression analysis performed with SPSS 18. Result from this study indicate that exchange rate of rupiah to dollar had negative effect on IHSG. World oil price had positive effect on IHSG. While the variables of inflation rate, SBI rate, world gold price and The Fed rate had no significant effect on IHSG. The value of adjusted R square is 50.2%. This means that 50.2% of IHSG movements can be predicted by the movement of the six independent variables.